Staffing levels and nursing‐sensitive patient outcomes: Umbrella review and qualitative study - Blume, Kai Svane; Dietermann, Karina; Kirchner‐Heklau, Uta; Winter, Vera; Fleischer, Steffen; Kreidl, Lisa Maria; Meyer, Gabriele; Schreyögg, Jonas (Health services research, 2021)
Objective To derive a comprehensive list of nursing‐sensitive patient outcomes (NSPOs) from published research on nurse staffing levels and from expert opinion. Data Sources/Study Setting Published literature reviews and their primary studies analyzing the link between nurse staffing levels and NSPOs and interviews with 16 experts on nursing care. Study Design Umbrella review and expert interviews. Data Collection/Extraction Methods We screened three electronic databases for literature reviews on the association between nurse staffing levels and NSPOs. After screening 430 potentially relevant records, we included 15 literature reviews, derived a list of 22 unique NSPOs from them, and ranked these in a systematic fashion according to the strength of evidence existing for their association with nurse staffing. We extended this list of NSPOs based on data from expert interviews. Principal Findings Of the 22 NSPOs discussed in the 15 included literature reviews, we rated the strength of evidence for four as high, for five as moderate, and for 13 outcomes as low. Four additional NSPOs that have not been considered in literature were identified through expert interviews. Conclusions We identified strong evidence for a significant association between nurse staffing levels and NSPOs. Our results may guide researchers in selecting NSPOs they might wish to prioritize in future studies. In particular, rarely studied NSPOs as well as NSPOs that were only identified through expert interviews but have not been considered in literature so far should be subject to further research.